Hikmah Tut Tasyri’ Ahli Waris Mualaf Setelah Pewaris Meninggal Dunia Mendapatkan Harta Warisan - yusida fitriyati (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
The causes of Islamic inheritance relationship are relationship nasab, marital relations, wala 'and the same religion relationship. Furthermore, the relationship causes a barrier of inheritance is for murder, different religions and slavery. From the above explanation if there are reasons the above relationship, it will cause a person entitled to be heirs and vice versa if there are causes obstructions inheritance, it will be blocked to inherit each other. If the heirs is not Moeslem and during heirs lifetime, and then heir embrace Islam, Mualaf. after He or She died while the inheritance is not devided yet. In this case there is a opinion of Imam mashab, which is the opinion of Imam Ahmad who argue are not blocked and the right to become heir. Based on the purpose of this research was conducted to know hikmahtut tasyri, Mualaf after the heir dies become heir. The Type of This research is a library (library research) by reviewing the current literature sources as data sources, which are analyzed descriptively qualitative. From results of this research, we concluded that hikmah tut tasyri Expected increase the confidence and faith of Islam heirs Mualaf, so strengthening his or her Islam. This is in keeping with religion. Adding and strengthen kinship between the heir to the heir who had died because there are two relationships that the same religion relationship and incest. These conditions will maintain the benefit of ancestry, making tranquility of life and love among the heirs.